Pressure change profile from laser induced shockwave using interferometer and intensity mapping - Yahya, Asiah; Munajat, Yusof (Faculty of Science, 2008)
Pressure change due to laser interaction can be measured using fringe analysis method which is reliable and accurate but rather time-consuming and also by the intensity mapping method which is a very fast and efficient but quite often plagued with phase ambiguity. In this work, the intensity mapping method was specially designed to eliminate phase ambiguity. Both methods of analysis are based on Abel inversion technique. Initially fringe analysis was seem to be more reliable but by around 5 (is delays both methods seemed to reach an agreeable value. The maximum pressure obtained from fringe analysis is 0.33 atm correspond to radius of 2.738 mm and from intensity mapping method is 0.244 atm corresponding to 2.526 mm.